Development of a novel component carrier selection algorithm in long term evolution-advanced (LTE-A) with carrier aggregation - Al Katsha, Mhd Zaher; Mohd. Ramli, Huda Adibah (Institute of Electrical and Electronics Engineers Inc., 2017)
Carrier Aggregation (CA), which is a method that aggregates multiple Component Carriers (CCs) of the same or different frequency bands, is one of the Long Term Evolution-Advanced (LTE-Advanced) key features. It allows the LTE-Advanced to support wider transmission bandwidth. Another important requirement is that the system needs to support a mixture of LTE-Advanced and the legacy Long Term Evolution (LTE) users simultaneously. The LTE-Advanced users can transmit packets on all of the available CCs whereas the LTE users are limited to transmit packets on a single CC. At the early stage of migration, there will be many LTE users in the LTE-Advanced system. Therefore, CC selection algorithm that is responsible to assign a CC to each newly-arrived legacy LTE users is becoming of paramount importance in the LTE-Advanced system. The existing CC selection algorithms can slightly provide good mobile cellular performance in terms of maximizing the throughput and balancing the load. To further improve the LTE-Advanced performance, this paper proposes a novel CC selection algorithm that takes the channel quality and traffic load in each CC into consideration. It was shown via simulation that the proposed algorithm can significantly improve the downlink LTE-Advanced performance as compared to the conventional CC selection algorithms.